Dissent : the history of an American idea - Young, Ralph F. (New York University Press, 2015)
"Dissent: The History of an American Idea examines the key role dissent has played in shaping the United States. It focuses on those who, from colonial days to the present, dissented against the ruling paradigm of their time: from the Puritan Anne Hutchinson and Native American chief Powhatan in the seventeenth century, to the Occupy and Tea Party movements in the twenty-first century. The emphasis is on the way Americans, celebrated figures and anonymous ordinary citizens, responded to what they saw as the injustices that prevented them from fully experiencing their vision of America. At its founding the United States committed itself to lofty ideals. When the promise of those ideals was not fully realized by all Americans, many protested and demanded that the United States live up to its promise. Women fought for equal rights; abolitionists sought to destroy slavery; workers organized unions; Indians resisted white encroachment on their land; radicals angrily demanded an end to the dominance of the moneyed interests; civil rights protestors marched to end segregation; antiwar activists took to the streets to protest the nation's wars; and reactionaries, conservatives, and traditionalists in each decade struggled to turn back the clock to a simpler, more secure time. Some dissenters are celebrated heroes of American history, while others are ordinary people: frequently overlooked, but whose stories show that change is often accomplished through grassroots activism. The United States is a nation founded on the promise and power of dissent. In this stunningly comprehensive volume, Ralph Young shows us its history"--Provided by publisher